Radioembolization and the Dynamic Role of 90Y PET/CT - Pasciak, Alexander S.; Bourgeois, Austin C.; McKinney, J. M.; Chang, Ted T.; Osborne, Dustin R.; Acuff, Shelley N.; Bradley, Yong C. (Frontiers in Oncology, 2014)
Before the advent of tomographic imaging, it was postulated that decay of 90 Y to the 0+ excited state of 90Zr may result in emission of a positron–electron pair. While the branching ratio for pair-production is small (~32 × 10−6), PET has been successfully used to image 90 Y in numerous recent patients and phantom studies. 90 Y PET imaging has been performed on a variety of PET/CT systems, with and without time-of-flight (TOF) and/or resolution recovery capabilities as well as on both bismuth-germanate and lutetium yttrium orthosilicate (LYSO)-based scanners. On all systems, resolution and contrast superior to bremsstrahlung SPECT has been reported. The intrinsic radioactivity present in LYSO-based PET scanners is a potential limitation associated with accurate quantification of 90 Y. However, intrinsic radioactivity has been shown to have a negligible effect at the high activity concentrations common in 90 Y radioembolization. Accurate quantification is possible on a variety of PET scanner models, with or without TOF, although TOF improves accuracy at lower activity concentrations. Quantitative 90 Y PET images can be transformed into 3-dimensional (3D) maps of absorbed dose based on the premise that the 90 Y activity distribution does not change after infusion. This transformation has been accomplished in several ways, although the most common is with the use of 3D dose-point-kernel convolution. From a clinical standpoint, 90 Y PET provides a superior post-infusion evaluation of treatment technical success owing to its improved resolution. Absorbed dose maps generated from quantitative PET data can be used to predict treatment efficacy and manage patient follow-up. For patients who receive multiple treatments, this information can also be used to provide patient-specific treatment-planning for successive therapies, potentially improving response. The broad utilization of 90 Y PET has the potential to provide a wealth of dose–response information, which may lead to development of improved radioembolization treatment-planning models in the future.